Documentos e memórias: uma arqueologia dos 50 anos do CECIMIG - Maria Angela Ribeiro Bosco Dumont (2016)
The record of human history and memory, be it personal, collective orinstitutional, is done through documents generated by activities that were developed by people in an institution and by the personal narratives of someone who was part of the story being recorded. Such records, when organized in an accessible way and facilitating there searches, become a powerful source of information for researchers and for society in general.The historical constructions are taken from original sources like documents that are archived and also from the daily things of the private life of people who work in an institution or who have passed through it.This information is the essence of an institution, organization or company and they are the memory of a society. In this direction, this research has as main objective to inventory some documents of CECIMIG and propose a way to organize them so that they become a rich source of information, more agile and accessible to the interested parties and at the same time, they will allow us tore construct part of the history of the referred center.The main conceptual references that we reused as subsidies to thediscussions carried out in this work involve the concepts of archive, document, history, memory and narrative. For the construction of the data, first an inventory of the documents filed in 192 boxes and the CECIMIG current file was carried out. From these files were selected minutes, resolutions, ordinances, projects and activity reports to be used in the next step. Thus, in the next phase of the research was conceived and executed an organization proposal of these documents, following athematic and chronological order. This way of organizing the archives allowed us to make a reconstruction of part of the history of CECIMIG from an archaeological analysis of the documents. Over the course of its 50 years of existence, about 268 teachers training actions have been developed at the Center, including upgrading, improvement andspecialization courses. The total duration of these courses was about 22,720 class hours, serving around 25,673 students/teachers.